Unfolding and displaying the influencing factors of advance directives from the stakeholder's perspective: A concept mapping approach. (17th May 2019) - Chan, Carmen W. H.; Choi, Kai C.; Chan, Helen Y. L.; Wong, Martin M. H.; Ling, Gigi C. C.; Chow, Ka M.; Chow, Amy Y. M.; Lo, Raymond; Sham, Michael M. K.
Abstract: Aims: To develop a culturally relevant conceptual map to discover perceptions of a statutory form of advance directive (AD) for Hong Kong Chinese. Design: This was the first study on AD using a concept mapping approach with two phases. Methods: The data collection of the two phases was conducted from February 2016–February 2017. In Phase I, 96 participants were recruited using purposive sampling. In Phase II, multi‐dimensional scaling and hierarchical cluster analysis were used to create a concept map based on quantitative data. Results: The map depicted six clusters of factors affecting the acceptance of AD, with their importance rating in decreasing order: Conditional factor, value system, process of AD, physical and illness factor, personal situation factor, and socio‐cultural factor. Conclusion: The study adopted a comprehensive approach to unfolding the multi‐faceted factors affecting the acceptance of ADs by stakeholders. Strategies targeting the clusters could be developed to facilitate the discussion and completion of AD. 摘要: 目的: 运用文化相关概念映射法, 研究中国香港预留医疗指令(AD)法定形式认知。 设计: 本研究是首次利用两阶段概念映射法研究预留医疗指令 方法: 本研究两阶段于2016年2月至2017年2月进行数据收集。第一阶段采用有目的抽样法聘请96名参与者;第二阶段基于定量数据采用多维尺度及层次集群分析来创建概念映射。 结果: 将描述六组集群的映射按其重要性递减顺序排列, 其中这六组集群是影响预留医疗指令接受的一些因素合集:条件因素、价值体系、预留医疗指令的过程、生理及疾病因素、个人情况因素和社会文化因素。 结论: 本研究采用综合法揭示影响股东接受预留医疗指令的多层面因素。开发针对集群的策略有助于促进讨论以及实现预留医疗指令。